2005
DOI: 10.1007/s10350-005-0202-x
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Tumor Markers for Proliferation and Apoptosis in Predicting Survival in Colorectal Cancer

Abstract: Colon cancer and rectal cancer seem to have different biologic behavior, at least with respect to apoptosis, cytoplasmic p53 expression, and perhaps Ki-67 and carcinoembryonic antigen. Further studies are needed to clarify the significance of these factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 43 publications
(45 reference statements)
6
56
1
Order By: Relevance
“…This fact suggests a different behaviour for telomerase depending on its localization ( Table 2). The findings of the present study are in accordance with other studies that identified differences in the etiologic, pathologic, and clinical behaviour of colon and rectal tumours: local recurrence occurs more frequently in patients with rectal cancer, and distant metastases occur more frequently in patients with colon cancer [73][74][75] . It is, therefore, reasonable to suggest that the etiologic factors and molecular bases may differ between colon and rectal cancers [72] .…”
Section: Telomerase As a Colorectal Cancer Markersupporting
confidence: 92%
“…This fact suggests a different behaviour for telomerase depending on its localization ( Table 2). The findings of the present study are in accordance with other studies that identified differences in the etiologic, pathologic, and clinical behaviour of colon and rectal tumours: local recurrence occurs more frequently in patients with rectal cancer, and distant metastases occur more frequently in patients with colon cancer [73][74][75] . It is, therefore, reasonable to suggest that the etiologic factors and molecular bases may differ between colon and rectal cancers [72] .…”
Section: Telomerase As a Colorectal Cancer Markersupporting
confidence: 92%
“…We observed an expression of p53 in 63% of the colorectal carcinomas which is in line with previous studies, where a range of 40 to 81% p53 positivity was found (10)(11)(12)(13). This wide range depends on different techniques used in these studies, such as different antibodies, scoring systems, cutoff-values and study populations.…”
Section: Discussionsupporting
confidence: 91%
“…Other studies reported an unfavourable prognosis in patients with p53-positive carcinomas (12,13,(24)(25)(26)(27)(28), but only few multivariate analyses yielded a significant result in these studies (25). However, other authors did not found a correlation of p53 and prognosis (11,16,29,30). Additionally, we observed that patients with p53-positive carcinomas tended to have a better recurrence-free survival.…”
Section: Discussioncontrasting
confidence: 55%
“…40 Although histologic grades have been shown to be significantly associated with prognosis, 2,40 the ambiguity of intermediate-grade tumors 55,67 and the marked degree of interobserver variation, with as low as 50% agreement between pathologists in some studies, have led to questioning of the relevance of the current histologic grading system. 23,36,37 The propensity for uncontrolled cellular proliferation is a hallmark of cancer, 17 and as such, measures of cellular proliferation have been used extensively to prognosticate both human 14,18,19,41,46,47,63,64 and veterinary neoplastic diseases. 1,3,20,22,24,26,29,34,49,52,53,56 In veterinary medicine, the most commonly used methods to evaluate cellular proliferation include proliferating cell nuclear antigen (PCNA) and Ki67 immunostaining and argyrophilic nucleolar organizing region (Ag-NOR) histochemical staining.…”
mentioning
confidence: 99%